Формування здорового способу життя у здобувачів вищої освіти - Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Verkholantseva, Valentyna; Мілаєв, Олександр Іванович; Милаев, Александр Иванович; Milaiev, Oleksndr; Мілаєва, Ірина Іванівна; Милаева, Ирина Ивановна; Milaieva, Iryna (ТДАТУ, 2021)
UK : У статті розглянута популяризація здорового способу життя здобувачів вищої освіти в університеті. EN : The article considers the promotion of a healthy lifestyle of higher education students at the university Key words: higher education seeker, student youth, student self-government, management, youth organization, public action.
Formation of a healthy lifestyle for higher education students
Keywords: здобувач вищої освіти; студентська молодь; фізичне виховання; студентські спортивні гуртки; спорт; фізична культура; здоров’я; higher education seeker; student youth; physical education; student sports clubs; sports; physical culture; health